Determinan Entrepreneurial Commitment: Peran Perceived University Support, Self-Efficacy, dan Social Support terhadap Entrepreneurial Intention Mahasiswa PMW UNJ - Ridwan Tamim Ismail; Annisa Lutfia; Rizka Zakiah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the influence of perceived university support, entrepreneurial self-efficacy, and social support on entrepreneurial intention, and the subsequent effect of entrepreneurial intention on entrepreneurial commitment among students funded through the Student Entrepreneurship Program (PMW) at Universitas Negeri Jakarta (UNJ). The study responds to a field finding that 63% of funded student businesses discontinued after the funding period ended, indicating that entrepreneurial commitment has not been optimal. Using an associative quantitative design, data were collected from 160 PMW UNJ participants from the 2024 and 2025 cohorts, selected through proportional random sampling, and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that perceived university support has no significant effect on entrepreneurial intention, whereas entrepreneurial self-efficacy and social support both have positive and significant effects, with self-efficacy as the strongest predictor. Entrepreneurial intention, in turn, has a strong positive and significant effect on entrepreneurial commitment. The model explains 29.0% of the variance in entrepreneurial intention and 59.6% of the variance in entrepreneurial commitment, with an overall large model fit. These findings suggest that PMW UNJ should strengthen self-funding training, personalized mentoring, and post-funding incubation to sustain student business commitment